2012
DOI: 10.1105/tpc.112.096610
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Arabidopsis Augmin Complex Uncovers Its Critical Function in the Assembly of the Acentrosomal Spindle and Phragmoplast Microtubule Arrays

Abstract: Plant cells assemble the bipolar spindle and phragmoplast microtubule (MT) arrays in the absence of the centrosome structure. Our recent findings in Arabidopsis thaliana indicated that AUGMIN subunit3 (AUG3), a homolog of animal dim gtubulin 3, plays a critical role in g-tubulin-dependent MT nucleation and amplification during mitosis. Here, we report the isolation of the entire plant augmin complex that contains eight subunits. Among them, AUG1 to AUG6 share low sequence similarity with their animal counterpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 59 publications
4
112
0
Order By: Relevance
“…g-Tubulin localization to phragmoplast MTs is largely dependent on augmin as it becomes dissociated from the phragmoplast in augmin mutant cells in A. thaliana [42 ]. In the mutant, the phragmoplast MT array often fails to expand toward the cell periphery and MTs ultimately became disorganized [42 ]. Similarly when genes encoding augmin subunits are silenced in the moss P. patens, phragmoplast expansion is inhibited because of compromised MT formation in the array [43 ].…”
Section: Amplification Of Mts At the Phragmoplast Peripherymentioning
confidence: 99%
See 1 more Smart Citation
“…g-Tubulin localization to phragmoplast MTs is largely dependent on augmin as it becomes dissociated from the phragmoplast in augmin mutant cells in A. thaliana [42 ]. In the mutant, the phragmoplast MT array often fails to expand toward the cell periphery and MTs ultimately became disorganized [42 ]. Similarly when genes encoding augmin subunits are silenced in the moss P. patens, phragmoplast expansion is inhibited because of compromised MT formation in the array [43 ].…”
Section: Amplification Of Mts At the Phragmoplast Peripherymentioning
confidence: 99%
“…The 8-subunit complex augmin contains a MAP and serves as a docking factor for the g-tubulin complex to localize to spindle MTs in animal and plant cells [40,41 ,42 ]. g-Tubulin localization to phragmoplast MTs is largely dependent on augmin as it becomes dissociated from the phragmoplast in augmin mutant cells in A. thaliana [42 ]. In the mutant, the phragmoplast MT array often fails to expand toward the cell periphery and MTs ultimately became disorganized [42 ].…”
Section: Amplification Of Mts At the Phragmoplast Peripherymentioning
confidence: 99%
“…For example, GRMZM2G311883 is a gene homologous to Arabidopsis MODIFIER OF SNC1-1 14 (MOS14), which is known to form a link between splicing and RNAdependent DNA methylation . Also, genes involved in cell cycle regulation, such as CYCD4, APC10, TIP120-encoding (Wang et al, 2011b), FORMIN8-like (Xue et al, 2011), and AUGMIN6-like (Hotta et al, 2012), are represented in the data set, as are developmental processes affecting the vasculature (Petricka et al, 2008), meristem maintenance , and cell shape and plant architecture (O'Hara et al, 2013). Several genes that are differentially methylated in the older zones play a known role in development.…”
Section: Differential Methylation Along the Developing Maize Leaf Potmentioning
confidence: 99%
“…Results from mutant studies suggest that GIP1a may increase the nucleation capacity of g-TuRCs in vivo (Nakamura et al, 2012). Many of the proteins that direct the localization or activity of g-TuRCs turn out to be essential genes (Ho et al, 2011;Hotta et al, 2012;Nakamura et al, 2012;Walia et al, 2014), indicating a critical role for the spatiotemporal regulation of g-TuRC-dependent microtubule nucleation in plant cells.…”
Section: Microtubule Nucleationmentioning
confidence: 99%
“…The AUGMIN complex, composed of six subunits common to all eukaryotes and two plant-specific subunits (Hotta et al, 2012), was initially found to recruit g-TuRC to microtubules within the mitotic spindle and the phragmoplast (Ho et al, 2011). Further work revealed that this complex recruits g-TuRC to interphase microtubules to promote nucleation activity (Liu et al, 2014).…”
Section: Microtubule Nucleationmentioning
confidence: 99%